Development of An Portfolio Electronic (Potret) Using Google Sites to Optimize Kindergarden Teacher Administration in Cisaat Sub-District, Sukabumi Regency - Rani Nurhikmah; Endin Mujahidin; Hendri Tanjung (Universitas Al-Hikmah Indonesia, 2025)
The development of information technology has brought significant changes in various aspects of education, including teacher administration in Kindergarten. Teacher administration that is still carried out manually often faces problems of efficiency, accessibility, and regularity in document management. To overcome these challenges, this study aims to develop an Electronic Portfolio (POTRET) based on Google Sites to support the digitization of kindergarten teacher administration. This research uses a Research and Development (R&D) approach by adopting the Borg & Gall model and the ADDIE model in product development. The subject of the study is a kindergarten teacher in Cisaat District, Sukabumi Regency, who already has an Belajar.id account from the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek). Data was collected through observations, interviews, questionnaires, and trial implementations of the POTRET system. The results of the study are expected to show that the implementation of an electronic portfolio based on Google Sites can improve the efficiency of teacher administration in compiling, storing, and accessing digital documents more systematically. In addition, this study also aims to evaluate the feasibility and effectiveness of POTRET in facilitating the administrative tasks of kindergarten teachers. The findings of this study are expected to contribute to the innovation of digitalization of early childhood education administration and support digital transformation policies in the education sector